The Renminbi Central Parity: An Empirical Investigation - Yin-Wong Cheung; Cho-Hoi Hui; Andrew Tsang (Center for Economic Studies and ifo Institute (CESifo), 2016)
On August 11 2015, China revamped its procedure of setting the official central parity of the renminbi (RMB) against the US dollar. Our empirical investigation shows that the intertemporal dynamics of China's central parity are not the same before and after this policy change. They are more variable and have a few new determining factors. Both the deviation of the RMB offshore rate from the central parity and the US dollar index are the two significant determinants of the central parity both before and after the policy change. The VIX index has explanatory power before August 2015, but not after. After August 2015, the onshore RMB rate and the difference between the one-month offshore and onshore RMB forward points show a significant impact on the central parity. While the US dollar index effect remains, we find no evidence of a role for the RMB exchange rate against the currency basket revealed by China in December 2015 in the fixing process.
Keywords: F31; F33; G15; G17; G18; 330; China; RMB; exchange rate policy; central parity rate; on-shore and off-shore rates